Local detection of defects from image sequences - Rafajłowicz, Ewaryst (1953- ); Wnuk, Marek; Rafajłowicz, Wojciech (Zielona Góra: Uniwersytet Zielonogórski)
Our aim is to discuss three approaches to the detection of defects in continuous production processes, which are based on local methods of processing image sequences. These approaches are motivated by and applicable to images of hot metals or other surfaces, which are uniform at a macroscopic level, when defects are not present.
Keywords: image processing; fractal dimension; morphological operations